New Accounting Reports: Sustainability and Integration in Artificial Intelligence (AI) Perspective: Theory accounting - Ika Simatupang; Diah Utami Kusuma Wardani; Iskandar Muda; Adi Syah Putra (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2025)
The increasing emphasis on environmental, social, and governance (ESG) issues has accelerated a shift from traditional financial reporting toward sustainability reporting and integrated reporting as part of new accounting reports. Conventional accounting reports are increasingly perceived as insufficient to capture long-term value creation and broader corporate impacts. This study aims to examine the role of Artificial Intelligence (AI) in enhancing sustainability reporting and integrated reporting within the framework of modern accounting practices. Using a Systematic Literature Review (SLR) approach, this study synthesizes peer-reviewed international journal articles published between 2020 and 2025 and indexed in reputable databases such as Scopus, Web of Science, and ScienceDirect. The findings reveal that AI substantially improves the quality of sustainability reporting through automated ESG data collection, real-time validation, anomaly detection, and advanced analytical capabilities, thereby reducing reporting errors and mitigating greenwashing risks. Moreover, AI facilitates the integration of financial and non-financial information by enabling data connectivity, predictive modeling, and materiality assessment, which strengthens the effectiveness of integrated reporting and supports strategic decision-making. Despite these benefits, the study identifies several challenges related to AI adoption, including algorithmic bias, limited digital infrastructure, insufficient assurance standards for AI-generated outputs, and organizational readiness, particularly in developing economies. Overall, the results support the New Accounting Reports perspective, which emphasizes sustainability and integration as essential elements of contemporary accounting reporting. This study contributes to the accounting literature by positioning AI as a strategic enabler of sustainable and integrated reporting and offers practical implications for regulators, practitioners, and researchers in developing governance frameworks and assurance mechanisms for AI-driven accounting reports. Keywords :Artificial Intelligence; Sustainability Reporting; Integrated Reporting; ESG; New Accounting Reports